2006
DOI: 10.1097/00129689-200608000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Intussusception due to Gastrointestinal Stromal Tumor (GIST) Treated by Laparoscopic Billroth II Distal Gastrectomy

Abstract: Gastrointestinal stromal tumors are rare tumors of the gastrointestinal tract. They, however, occur most commonly in the stomach where they present with abdominal pain, bleeding, and obstruction. Many are asymptomatic and are discovered incidentally or at postmortem. We present a case-report of a rare complication of gastrointestinal stromal tumors of the stomach causing gastroduodenal intussusception and how patient was successfully managed by laparoscopic Billroth II distal gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The other case was an 84-year-old male who presented with a six-week history of intermittent colicky abdominal pain, nausea and vomiting. The tumor was located in the antrum and was successfully managed with Billroth II resection (6). In our case, the tumor was located in the proximal antrum, and she had been having intermittent epigastric discomfort associated with nausea and vomiting, suggestive of intermittent gastric outlet obstruction.…”
mentioning
confidence: 66%
“…The other case was an 84-year-old male who presented with a six-week history of intermittent colicky abdominal pain, nausea and vomiting. The tumor was located in the antrum and was successfully managed with Billroth II resection (6). In our case, the tumor was located in the proximal antrum, and she had been having intermittent epigastric discomfort associated with nausea and vomiting, suggestive of intermittent gastric outlet obstruction.…”
mentioning
confidence: 66%
“…There was one report in which a laparoscopic distal gastrectomy with Billroth-II anastomosis was performed for anantral GIST, which served as the lead point for agastroduodenal intussusception. (5) In our case laparoscopic wedge resection with eversion method was performed.…”
Section: Discussionmentioning
confidence: 79%
“…If the cause of the intussusception is easily reducible, symptoms canbe more intermittently developed with mild degree. (5) Otherwise, if the lesion is too large to be reduced by itself, prolonged symptoms of upper gastrointestinal obstruction and even pancreatitis may develop. (1) Our patient presented a 3-day history of symptoms and pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative diagnosis of gastroduodenal intussusception caused by gastric tumors can be difficult and may require different modalities of investigation, including CT and endoscopy. 4 Gastric tumors may be detected by upper gastrointestinal endoscopy as an endophytic mass protruding into the lumen, or even the full thickness of the gastric wall extending into the duodenum, and most patients can undergo endoscopic reduction. Unlike endoscopy, CT can provide details of the intussusception and the adjacent organs and is critical for the preoperative assessment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of gastroduodenal intussusception caused by gastric GIST mainly includes surgical resection and endoscopic treatment. Twenty-two previous cases 3 – 5 , 15 33 were treated by surgical resection and only two cases 11 , 14 were treated by endoscopic submucosal dissection (ESD). Notably, 12 cases underwent laparoscopic surgery, but no studies have reported the use of a robotic approach.…”
Section: Discussionmentioning
confidence: 99%